Interstitial brachytherapy for internal mammary node in breast cancer: A case report - Pandit, Subhas; Sapkota, Simit; Suwal, Sundar; Adhikari, Abish; Karki, Prakriti; Kumar, Anjani (Journal of Contemporary Brachytherapy, 2023)
This case study reports the feasibility, safety, and efficacy of interstitial brachytherapy for internal mammary nodal recurrence in a 68-year-old woman with triple-negative breast cancer. The patient had previously undergone mastectomy followed by chemotherapy and radiotherapy. However, an internal mammary node was discovered during a routine follow-up a year later, which was confirmed as metastatic carcinoma by fine needle aspiration, with no other metastatic lesions. The patient underwent interstitial brachytherapy under ultrasound and computed tomography (CT) guidance, with a prescribed dose of 20 Gray in one fraction. Follow-up CT scan imaging over a 2-year period of treatment showed a complete resolution of internal mammary node. Therefore, brachytherapy may be considered a potential treatment option for cases of isolated internal mammary node recurrence in breast cancer.